Prime Identification in Historical Languages: : The Old English Exponent for the Semantic Prime DIE - Mateo Mendaza, Raquel (International Journal of English Studies, 2025)
This research focuses on the identification of the Old English exponent for the semantic prime DIE following the approach of the Natural Semantic Metalanguage theory (Goddard, 2008, 2011; Wierzbicka, 1996). The aim of this paper is to complete the research begun on Old English exponents for the category Life and Death and to review the methodology applied in previous research on this field, which is based on morphological, textual, semantic and syntactic criteria and on the search for examples of the exponent word within the alternative syntactic configurations associated with the prime. The fact that DIE is the only predicate prime which does not allow for optional arguments entails the implementation of a new methodological approach to determine the suitability of the verb selected as prime exponent. All in all, the conclusion is drawn that the OE verb sweltan is selected as the exponent of DIE in Old English.